Paediatric pancreatic problems: A five-year experience - Lahoti B; Aggarwal Gaurav; Satsangi Bhaskar; Sudarania Manoj; Sharma Shashi; Upadhyaya V; Mathur R (Wolters Kluwer Medknow Publications, 2010)
Background: To analyse a tertiary care experience with various pancreatic problems in the paediatric age group and clarify the frequency of various pancreatic diseases in the same patient population as well as the role of surgical or conservative management in their treatment. Patients and Methods: All patients with clinical suspicion of disease pertaining to the pancreas, substantiated by laboratory investigations or imaging modalities over a period of five years are included in our study. Results: Of the total 228 patients with various pancreatic problems, who presented to us, mostly with acute pancreatitis and pancreatic trauma, 64 needed surgical interventions. The total mortality rate encountered was a meagre 3.5%. Conclusion: Paediatric pancreatic disorders are not so infrequent; and a high index of suspicion aided by the newer modalities of investigation greatly helps in the appropriate and timely management.